Modulation in the Protein Metabolism under Sublethal Concentration of Quinalphos Intoxication in the Freshwater Common Carp, Cyprinus carpio (Linnaeus, 1758) - David, Muniswamy (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe fresh water field fish, Cyprinus carpio is an important human food source in parts of South India and the fish is constantly exposed to pesticides, which are used extensively to control agricultural pests. Freshwater edible fish, Cyprinus carpio were exposed to sublethal concentration (0.75 Âµl/L) of commercial grade quinalphos (25% Emulsified Concentration) for 5, 10 and 15 days. Liver being the main site of metabolic activity in body and highly active in both toxifying and detoxifying insecticides, was selected for the study purpose. After each exposure periods, liver was taken to study biochemical alterations. Increase in free amino acid, protease activity and Ach levels, in contrast to decrement in total, structural and soluble proteins and acetylcholinesterase (AchE) activity were observed in 5 and l0 day of exposure, but on 15 day of exposure all the values reached nearer to normal condition. Restoration of protein fractions, free amino acid, protease activity, acetylcholine (Ach) and acetylcholinesterase (AchE) levels to normal, implies that after 10 day of exposure there seems to exist an oscillatory phase in protein turnover towards a more synthetic phase leading to the establishment of recuperation and adaptation phenomena. Thus it is inferred that exposure to quinalphos in sublethal doses affect protein metabolism and normal neural physiology of the liver. But recovery in later periods may be revitalization phenomenon as every organism strives to overcome the stress to prove its existence. Recovery phenomenon may be adaptive and even strategic.